Nuclear receptor superfamily: structural insights into function - Moras, Dino (Henry Stewart Talks, 2007)
Signal transduction and transcriptional regulation, Cofactor binding and transcriptional activation, The modular organization of nuclear hormone receptors, The DNA binding domain, The ligand binding domain, Sequence/structure to function, The oligomeric state, Allosteric control through post-translational modifications, Communication pathways in NRs, Ligand binding: specificity and adaptability, The retinoid receptors: RXR and RAR, Structural adaptability in the ligand-binding pocket of the ecdysone hormone receptor, Binding to coactivators and corepressors: the signature motifs, Ligand dependent (de)activation: agonists and antagonists, Estrogen receptor, The vitamin D receptor
Archived at 2020/08/13